PENGARUH PHYSICAL WORK ENVIRONMENT DAN WORK EXPERIENCE TERHADAP WORK PERFORMANCE MELALUI ACHIEVEMENT MOTIVATION SEBAGAI VARIABEL MEDIASI(Studi kasus pada PT Jakarta Tourisindo Unit d' Arcici Hotel Al Hijra Cempaka Putih) - Seno Jati Prakoso (2022)
This study is a quantitative study that aims to determine whether there is an influence between physical work environment and work experience on work performance with achievement motivation as mediating variable employee of PT Jakarta Tourisindo Unit d'Arcici Hotel Al Hijra Cempaka Putih. The study used a total of 75 respondents, the sampling technique used was saturated sampling technique. The analysis technique used is path analysis and data processing which is carried out through SmartPLS3.0. The results of the test obtained (1) physical work environment has significant effect on work performance of employee of PT Jakarta Tourisindo Unit d'Arcici Hotel Al Hijra Cempaka Putih, (2) work experience has significant effect on work performance of employee of PT Jakarta Tourisindo Unit d'Arcici Hotel Al Hijra Cempaka Putih, (3) physical work environment has significant effect on achievement motivation of employee of PT Jakarta Tourisindo Unit d'Arcici Hotel Al Hijra Cempaka Putih, (4) work experience has significant effect on achievement motivation of employee of PT Jakarta Tourisindo Unit d'Arcici Hotel Al Hijra Cempaka Putih, (5) achievement motivation has significant effect on work performance of employee of PT Jakarta Tourisindo Unit d'Arcici Hotel Al Hijra Cempaka Putih. As for the indirect significant effect between physical work environment and work experience on work performance through achievement motivation. Keywords: Work Performance, Physical work environment, Work Experience dan Achievement Motivation